Efficacy of the combination of water aerobics and metacognitive training on psychological and physical health variables and their relationship with SP1 and SP4 biomarkers in people with psychosis: a study protocol - Ochoa, Susana; Verdaguer-Rodríguez, Marina; Batlle, Núria; Garreta, Francesc; Garcia, Berta; Haro, Josep María; Vila-Andreu, Èlia; Hernández, Maria José; Escandell, Maria José; Muñoz, Ana; Vilamala, Sònia; Marcos, Sandra; et al. (Frontiers in Psychology, 2024)
Background: Metacognitive Training (MCT) is widely used and effective in reducing positive symptoms in psychosis. Physical exercise, such as Water Aerobics (WA), improves general health, quality of life and symptoms as a low impact activity that allows social interactions. Preliminary results suggest a relationship between dopamine and psychotic symptoms, through SP transcription factors, SP1 and SP4 biomarkers. The aims of the project are to evaluate the efficacy of a combined intervention (WA and MCT) for psychosis to improve psychotic symptoms, physical health, and transcription levels of SP biomarkers.Material and methods: This is a unicentric randomized controlled trial of three parallel intervention groups: MCT, WA and combined intervention. The estimated sample will be 48 patients with a psychotic spectrum disorder diagnosis. The assessment will be performed at baseline and at 3-months' follow-up. Instruments used in the assessment will include clinical, cognitive, metacognitive, social cognitive and psychosocial variables.Discussion: This will be the first study investigating the impact of the combination of MCT and WA in psychosis. Moreover, it will be the first study analyzing changes in the transcriptional biomarkers SP1 and SP4 after interventions. The results of this study may have clinical implications contributing to the improvement of treatment selection. Clinical trials registration: [https://clinicaltrials.gov/], identifier [NCT05455593].